Collective identities in political-media discourse in Venezuela: Aló, Presidente and the representation of Venezuelan society - Ramírez Lasso, M. Lilia (Romanica Olomucensia, 2015)
Political and media discourse has a key role in the process of the reconfiguration of the Venezuelan public sphere and the transformation of society and political representation currently going on in Venezuela. This process implies the symbolic construction of new social identities (people, oligarchy), political identities (chavistas, revolutionaries; opposition, antichavistas), and government identities (consejos comunales, comunas), as well as the construction of new meanings in another group of social identities (afrodescendants, farmers, fishers, students, women, ancestral peoples, poor people, and others). Then it is important to study the construction of this group of identities in a public space, mediated by ICT (Information and communications technology), such as Aló, Presidente, which had a significant impact on the media and communication in Venezuela during the government of President Hugo Chávez. In this paper some notions of Critical Discourse Analysis (CDA) are applied to the study of the discourse categories used to configure these collective identities, as well as the visual categories that allow adhesion to a group to be seen through such significant systems as clothing and gestures in the broadcasts of 2010 of this public space.
Keywords: Venezuela; Aló; Presidente; identity; collective; political discourse; media.